A new species of tree frog (Genus: Polypedates) from Great Nicobar, India (Anura: Rhacophoridae) - Das, I. (Centre for Herpetology, Madras Crocodile Bank Trust, 1995)
A new species of tree frog of the genus Polypedates is described on the basis of 11 examples collected from Great Nicobar Island, India. The new species is diagnosed by the following characteristics: large body size (female SVL <65.2 mm; male SVL <43.3 mm), head broader than long, and lacking a bony crest; concave lores; eye diameter less than the eye-nostril distance, tympanum diameter less than ¾ eye diameter; toes 2/3 webbed; toe IV with one phalange free, absence of outer metatarsal tubercle; tibio-tarsal articulation reaches the nostrils; no tubercles on the undersurface of the arm and dorsum typically with a dark hour-glass marking.